Reel World : An Anthropology of Creation - Pandian, Anand (Book collections on Project MUSE., 2015)
With an adventurous writing style, Anand Pandian explores the transformative potential of cinema, following Tamil films from the spark of artistic impulse through their production, marketing, and reception to show how cinema recasts the ordinary experience of everyday life.